Economic Valuation for Cidanau Watershed Area, Indonesia - Kunihiko Yoshino; Budi Indra Setiawan; Hideki Furuya (Institut Pertanian Bogor (IPB University), 2010)
The paper describes economic valuation for the Cidanau watershed area of West Java in Indonesia. In this area natural resources deterioration has occurred even faster after the Asian Financial Crisis. The deforestation area and pronounced soil erosion seems to go unhindered because of land use competition among the residents for agricultural space, housing, etc. In order to prevent the area from further degradation, the purpose of this paper is to carry out quantitative evaluation which also attempts to raise the environmental awareness of residents, as well as visitors to the area. Questionnaire surveys were conducted and analyzed according to the Contingent Valuation Method (CVM) and the Travel Cost Method (TCM). The results show all respondents held good attitudes towards the efforts of environmental conservation, but responded negatively if they had to contribute to the environmental service payment. Visitors to the Anyer Beach acted differently because most of them come from faraway locations and have little knowledge of the watershed. However, the Anyer Beach recorded an environmental valuation of about Rp840 billion, which is a potential source for the service payment of Cidanau watershed.